Structural Model of the Relationship Between Social Anxiety in University Students and Self-Criticism, Shame, with the Mediating Role of Emotion Regulation and Self-Esteem - Khoshkam, Zahra; khoshkam, Samindokht; Honarparvaran, Nazanin (Mental Health and Lifestyle Journal, 2024)
The present study aimed to investigate a structural model explaining social anxiety among university students based on self-criticism and shame, with the mediating roles of emotion regulation and self-esteem. This study employed a descriptive-correlational design using structural equation modeling (SEM). The statistical population consisted of university students in Tehran during the 2025–2026 academic year, from which 360 participants were selected through multistage cluster random sampling. Data were collected using standardized instruments including the Social Anxiety Scale, Levels of Self-Criticism Scale, Experience of Shame Scale, Difficulties in Emotion Regulation Scale, and Rosenberg Self-Esteem Scale. Descriptive statistics and Pearson correlation coefficients were calculated using SPSS-27, and SEM analyses were conducted using AMOS-24. Model fit was evaluated using indices such as χ²/df, CFI, TLI, NFI, and RMSEA. Mediation effects were tested through bootstrapping procedures with 2000 resamples. The results indicated that self-criticism (β = 0.31, p < 0.001), shame (β = 0.24, p < 0.001), and emotion regulation difficulties (β = 0.28, p < 0.001) had significant positive direct effects on social anxiety, whereas self-esteem had a significant negative effect (β = -0.26, p < 0.001). Additionally, emotion regulation and self-esteem significantly mediated the relationships between self-criticism and social anxiety, as well as between shame and social anxiety (p < 0.01). The proposed structural model demonstrated good fit to the data (χ²/df = 2.41, CFI = 0.94, TLI = 0.92, NFI = 0.91, RMSEA = 0.063). The findings support a comprehensive model in which self-criticism and shame contribute to social anxiety both directly and indirectly through emotion regulation difficulties and reduced self-esteem, highlighting the importance of targeting these mechanisms in psychological interventions.